3rd ICTs and Society Meeting; Paper Session - Theorizing the Internet; Paper 4: A Methodological Reflection on Converging Technologies and Their Relevance to Informa-tion Ethics - Pak-Hang Wong (tripleC: Communication, Capitalism & Critique)
In light of converging technologies, there is a clear sense that ethicists of various technological domains are coming together. Or, that they should come together. Yet, despite increasing cooperation and boundary-crossing in various fields of the ethics of technology, these efforts remain mostly at topical level. Relatively little attention has been given to issues on methodologies. The current paper aims to contribute to the current research by raising the methodological issues. In this paper, my objective is to argue that ethics of Information Technology (or Information Ethics (IE)) can benefit from the insights in other fields of the ethics of technology. Drawing the insights from other fields of the ethics of technology, I shall propose a systematic account of an Empirical Information Ethics (EIE)